2020
DOI: 10.1088/1742-6596/1504/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Mhd flow of nanofluids in the presence of porous media, radiation and heat generation through a vertical channel

Abstract: Aim of present study is to identify the effects of radiation and heat generation in unsteady MHD mixed convective flow of nanofluids along a upstanding channel through porous medium. Four types of nanofluids were studied (i) Water based – Ag (ii) Water based – Al2O3. Water is taken as convectional base fluid and Ag and Al2O3 particles are incorporated in this base fluid. Keeping in mind the congregating and random motion of nanoparticles, “Koo and Kleinstreuer model” is used. The main characteristics of the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It is suggested that for case of suction (s > 0) , the increase of s results to the boundary layer thinning while in the case of injection (s < 0) , the presence of injection effect has promoted to the drastically increases in the Table 1. Mathematical expression for empirical correlation of nanofluid [47][48][49] .…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that for case of suction (s > 0) , the increase of s results to the boundary layer thinning while in the case of injection (s < 0) , the presence of injection effect has promoted to the drastically increases in the Table 1. Mathematical expression for empirical correlation of nanofluid [47][48][49] .…”
Section: Resultsmentioning
confidence: 99%
“…By using Rosseland’s diffusion approximation for radiation and following methodology shown in 33 36 , the radiative flux is of the form where and are Stefan–Boltzmann values and the mean absorption factor. It is assumed that temperature variations within the flow are minimal enough to interpret the radiative flux’s fourth-power term as a linear function of temperature, as …”
Section: Methodsmentioning
confidence: 99%
“…The numerical Runge-Kutta solution using a shooting strategy was used to reach the main conclusions. The effect of thermal radiation dissipation on nanofluids in an unsteady MHD occupied by a permeable medium only along the upstanding conduit was examined 24 .…”
Section: Greek Symbols τmentioning
confidence: 99%